Acute Chagas disease induces cerebral microvasculopathy in mice. - Lindice Mitie Nisimura; Vanessa Estato; Elen Mello de Souza; Patricia A Reis; Marcos Adriano Lessa; Hugo Caire Castro-; Mirian Claudia de Souza Pereira; Eduardo Tibiriçá; Luciana Ribeiro Garzoni (Public Library of Science (PLoS), 2014)
Cardiomyopathy is the main clinical form of Chagas disease (CD); however, cerebral manifestations, such as meningoencephalitis, ischemic stroke and cognitive impairment, can also occur. The aim of the present study was to investigate functional microvascular alterations and oxidative stress in the brain of mice in acute CD. Acute CD was induced in Swiss Webster mice (SWM) with the Y strain of Trypanosoma cruzi (T. cruzi). Cerebral functional capillary density (the number of spontaneously perfused capillaries), leukocyte rolling and adhesion and the microvascular endothelial-dependent response were analyzed over a period of fifteen days using intravital video-microscopy. We also evaluated cerebral oxidative stress with the thiobarbituric acid reactive species TBARS method. Compared with the non-infected group, acute CD significantly induced cerebral functional microvascular alterations, including (i) functional capillary rarefaction, (ii) increased leukocyte rolling and adhesion, (iii) the formation of microvascular platelet-leukocyte aggregates, and (iv) alteration of the endothelial response to acetylcholine. Moreover, cerebral oxidative stress increased in infected animals. We concluded that acute CD in mice induced cerebral microvasculopathy, characterized by a reduced incidence of perfused capillaries, a high number of microvascular platelet-leukocyte aggregates, a marked increase in leukocyte-endothelium interactions and brain arteriolar endothelial dysfunction associated with oxidative stress. These results suggest the involvement of cerebral microcirculation alterations in the neurological manifestations of CD.